AB0409 Missing the big picture? an audit of hand x-rays in biologic treated rheumatoid arthritis patients. (12th June 2018) - Habib, U.; Sahni, A.; Lloyd, M.; Barber, B.; Cameron, J.; Melath, S.; Christidis, D.; Wajed, J.; Mistlin, A.; Cooper, S.
Abstract : Background: Rheumatoid arthritis (RA) treatment is target driven. The aim is to prevent joint damage and relieve pain and functional loss. X-ray (XR) erosions are an unambiguous sign of disease activity and progression. Objectives: We aimed to review our practice in looking for erosions in our biologic treated patients. We chose this group as they were likely to have the most severe and clearly defined RA. Methods: 100 random biologic treated patients from our biologics database were selected for analysis. We used patient letters and our digital imaging system (PACS) for further information. Our PACS has records running back to 2004. Results: Mean age was 58 years. 77% were female. Mean duration of RA was 10.6 years (range 0.9–44 years). 46 were currently receiving etanercept; 17 tocilizumab; 15 adalimumab; 14 certolizumab; 5 rituximab and 3 abatacept. 61 patients were current prednisolone users. The mean duration of biologic treatment was 4.8 years. 44 patients had received more than one biologic drug; 17 more than two. Mean DAS was 3.4. 72 patients had had previous documented hand XRs; 25 (34%) of these had erosions. The mean duration since the last hand XR was 37 months. 27 patients had had 2 previous hand XRs; 11 had had 3, 4 had had 4 and 2 had had 6 previous XRs. In 19 cases hand erosions appeared to have progressed in the patients who had had more than one XR. 44 patients had had previous foot XRs; 15 (34%) had erosions. 26 patients had had more than one foot XR. 36 patients had had previous joint ultrasound (US); in 17 (47%) US suggested active synovitis. The mean duration since the last US was 17 months. Conclusions: Our patients had relatively high disease activity despite biologic treatment, over half were also on steroids and significant numbers had had several biologic switches. Despite this only around two thirds of patients had had previous hand XRs documented over an average of 10 years RA duration, and there was a long average time since the last imaging. US rates were lower, but scans were more recent, perhaps suggesting a more modern trend to US over XR. Less than half of patients had had foot XRs. Although there was a lower rate of foot XRs the rate of erosions was similar in hand and foot XRs, suggesting similar patterns of joint damage. Interestingly, despite erosions being a hard end point in most treatment trials, NICE guidance only suggests XR early in RA in 'people with persistent synovitis' 1 and EULAR guidance suggests assessing for 'structural damage' without specifying time intervals. 2 Although newer imaging techniques may be more sensitive, XRs remain cheap, quickly accessible and allow objective assessment, particularly in long term patients being assessed for biologic switches. Our audit suggests that this well established and useful measure of disease burden may currently be relatively neglected. References: [1] https://www.nice.org.uk/guidance/qs33 [2] http://ard.bmj.com/content/early/2017/03/17/annrheumdis-2016-210715 Disclosure of Interest: None declared